Longitudinal systolic strain profiles and outcomes in peripartum cardiomyopathy. Issue 9 (25th June 2016) - Briasoulis, Alexandros; Mocanu, Marian; Marinescu, Karolina; Qaqi, Osama; Palla, Mohan; Telila, Tesfaye; Afonso, Luis
Abstract : Objective: Peripartum cardiomyopathy (PPCM) is a rare cause of heart failure that develops in the last month of pregnancy or within 5 months of delivery. Longitudinal systolic strain has been shown to be impaired in HF patients with both preserved and depressed EF, but has not previously characterized in patients with PPCM. Methods: The purpose of our study was to investigate the prognosis and recovery in patients with PPCM and use 2D strain imaging to characterize regional and global LV strain in patients with PPCM. Between 2009 and 2014, we identified 47 newly diagnosed patients with PPCM and reduced EF (rPPCM), and 14 patients within the first 4 weeks postpartum who presented with signs and symptoms of HF, and elevated BNP/pro‐NT‐BNP, but preserved LVEF (pPPCM). We compared the echocardiographic characteristics of the patients with rPPCM and pPPCM with 14 healthy controls. Results: All‐cause mortality was 10.6% (5/47) and rehospitalization for HF rate was 31.9% (15/47) at a median follow‐up of 12.5 months (range: 1–60 months) in the rPPCM group. In 25.5% (12/47) of patients with rPPCM, there was no recovery or worsening of LVEF, while complete and partial (more than 10% increase but less than 55%) recovery was seen in 57.4% (27/47) and 17% (8/47) of patients, respectively. Global and longitudinal strain (GLS) values were not independent predictors of all‐cause mortality or the composite endpoint of all‐cause mortality, rehospitalization, or no LVEF recovery in these patients. GLS and segmental strain were significantly lower in the preserved EF group compared with controls but higher compared with PPCM with reduced EF. Conclusion: Global and segmental longitudinal strain parameters were significantly reduced in PPCM patients.